2019
DOI: 10.1093/jee/toz297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interspecific Larval Competition on Developmental Parameters in Nutrient Sources Between Drosophila suzukii (Diptera: Drosophilidae) and Zaprionus indianus

Abstract: Two invasive drosophilids, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) and Zaprionus indianus (Gupta) (Diptera: Drosophilidae) are expanding their geographic distribution and cohabiting grape production in the Mid-Atlantic. The ecological and economic impact of these two species within vineyards is currently unknown. Zaprionus indianus was presumably not capable of ovipositing directly into grapes because they lack a serrated ovipositor and may use D. suzukii oviposition punctures for depositing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Studies of interspecific competition between D . suzukii and different species have shown different impacts [ 41 43 ], which raises the possibility that the effect of interspecific interaction is dependent on the species that co-occur with D . suzukii .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of interspecific competition between D . suzukii and different species have shown different impacts [ 41 43 ], which raises the possibility that the effect of interspecific interaction is dependent on the species that co-occur with D . suzukii .…”
Section: Introductionmentioning
confidence: 99%
“…suzukii and Z . indianus showed that to some extent, the performance of each species might depend on the substrate where they developed [ 43 ]. However, a structured study to analyze the competition between D .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the behavioral ecology and host use of this species has indicated that it is highly polyphagous and can feed and reproduce on a wide array of crop and non-crop host fruits (Lee et al, 2015). D. suzukii likely evolved its niche separation as a means of escaping intense interspecific competition from nearby and often overlapping temperate Drosophila (Shrader et al, 2020). While its sister species are highly competitive on overripe and rotting fruit, and indeed, D. suzukii is easily outperformed on those resources by D. melanogaster (Dancau et al, 2017), a move to intact fruit likely allowed D. suzukii to access resources otherwise avoided.…”
Section: Introductionmentioning
confidence: 99%
“…While conspecific larval density can (but not always does) increase protection against predators (Rohlfs and Hoffmeister 2004), it also increases intra-specific competition thereby decreasing resource availability (Atkinson and Shorrocks 1984; Klepsatel et al 2018), resulting in an inverse relationship with adult reproduction and population growth (i.e., ‘density-dependent effects’) [e.g., (Capinera and Barbosa 1977; Gage 1995; Baldal et al 2005; McGraw et al 2007; Morimoto et al 2016, 2017; Wigby et al 2016)]. Likewise, larval nutrition modulates larval growth as well as adult size, reproduction, and the expression of other fitness traits (‘diet-dependent effects’) (Cookman et al 1984; Greene 1989; Perkins et al 2004; Matavelli et al 2015; Rodrigues et al 2015; Silva-Soares et al 2017; Jang and Lee 2018; Morimoto et al 2019b, 2020; Shrader et al 2019). Therefore, herbivorous holometabolous insects can be excellent models to test the long-term consequences of the developmental environment in controlled experiments, from which the results can help advance ecological theory and thus be generalised to broader ecological contexts.…”
Section: Introductionmentioning
confidence: 99%